Krashen’s Theory of Second Language Acquisition as a Framework for Integrating Social Networking in Second Language Learning - Hamakali, Hafeni P. S. (IJRDO- Journal of Educational Research, 2017)
Social networking is a potential learning tool for second language learners as it provides them with extensive resources of authentic materials to complement language lessons. There is a growing interest in how social networking can be used for second language learning purposes. Second language acquisition (SLA) is a complex adaptive system as it can adapt to different conditions presented by both internal and external learning environments. Various SLA theories have been adapted to inform the design of different language learning tools. This paper analytically explains how Krashen’s theory SLA supports the effective use of social networking in language learning. There are various social networking sites on the Internet; however, this paper will mainly focus its reference to Facebook.